Impact of Wooden Versus Nonwooden Interior Designs on Office Workers' Cognitive Performance. Issue 1 (February 2020) - Shen, Jingyun; Zhang, Xi; Lian, Zhiwei
The biophilic hypothesis states that human beings have an innate connection to nature. Accordingly, previous studies have shown that natural interior design elements may influence the occupants' cognitive performance. This study investigated the effect of wooden elements on the occupant preference and cognitive performance of 20 adults (10 females and 10 males). Participants reported increased attention and productivity in wooden rooms versus a nonwooden room and were more likely to choose one of several wooden rooms over a concrete room as their preferred work environment. Participants also performed better on neurobehavioral tests in the wooden versus nonwooden environment. Participants' average completion times decreased on average by 16 seconds, 5 seconds, 6 seconds, 16 seconds, and 7 seconds, respectively, for tests of Visual Reaction, Continuous Operation, Stroop, Calculation, and Meaningless Picture Recognition tests in the wooden versus concrete environments. On all five tests, participants gave more correct answers in the three wooden settings than in the concrete one. These results support the biophilic hypothesis; incorporating wooden elements into interior design may improve both occupant satisfaction and cognitive performance.